2020
DOI: 10.3390/ijerph17228628
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Intensity, Frequency, Duration, and Volume of Physical Activity and the Risk of Stroke in Middle- and Older-Aged Chinese People: A Cross-Sectional Study

Abstract: Context: Persuasive evidence has shown the inverse associations between physical activity (PA) and the risk of stroke. However, few studies have investigated the associations between different dimensions (intensity, frequency, duration, volume) of PA and the risk of stroke. Objective: To investigate the associations between different dimensions of PA and the risk of stroke in total participants and subgroups. Method: This study included 6250 individuals aged 45 years old and above from the China Health and Ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
1
6
1
Order By: Relevance
“…20,21 The limited mechanization or services resources of housework in rural areas forced women to do most of housework, which fueled markedly increased the gender gap in income. 22 With age increasing, both old men and women may drop out of the labor market, so this gap in income would close and was not observed in our results among old participants. In China, the legal age for marriage is 20 for women but 22 for men, which may account for the higher marital SES-score in youth women.…”
Section: Discussioncontrasting
confidence: 53%
“…20,21 The limited mechanization or services resources of housework in rural areas forced women to do most of housework, which fueled markedly increased the gender gap in income. 22 With age increasing, both old men and women may drop out of the labor market, so this gap in income would close and was not observed in our results among old participants. In China, the legal age for marriage is 20 for women but 22 for men, which may account for the higher marital SES-score in youth women.…”
Section: Discussioncontrasting
confidence: 53%
“…Evidence suggested that the level of physical activity was associated with the risk of stroke, and light physical activity may not be related to the risk of stroke. 25–27 …”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggested that the level of physical activity was associated with the risk of stroke, and light physical activity may not be related to the risk of stroke. [25][26][27] The putative mechanism of diabetes's influence involves several aspects. The nitric oxide (NO)-mediated vasodilation is compromised among diabetic patients, resulting in endothelial dysfunction and a cascade reaction of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of exercise was calculated by multiplying the weekly frequency and the duration of each session according to prior research 20 . Regular exercise was defined as at least 150 minutes of moderate-intensity or 75 minutes of vigorous-intensity physical activity per week as recommended by the 2020 guidelines of the World Health Organization (WHO) 21 .…”
Section: Definition Of Healthy Lifestylesmentioning
confidence: 99%